The Ability of Students to Use an Android-Based Multimedia Learning Website Called "KELAS KITO" at Muhammadiyah University of Luring the Covid-19 Pandemic - washlurachim safitri; Aji Prayogo (Teaching English and Language Learning English Journal, 2021)
This study aims to determine how the impact of the COVID-19 pandemic on students' ability to use E- Learning. This research uses descriptive quantitative case study method that is used to get a picture of students' ability to use E-Learning. In this study, the respondents were 30 students, and gave them a multiple-choice test. The results of this study indicate that the ability of students to use E Learning is sufficient, but there are some problems in using E-Learning cannot be accessed on certain Wi-Fi, and then the E-Learning web is often error. Therefore, it can be concluded that students already have the ability to use E-Learning KELAS KITO, but on the other hand, students also find some problems that exist in the E-Learning.Keywords: Corona Virus, Online Learning, E-Learning KELAS KITO